EEG Response to Sedation Interruption Complements Behavioral Assessment After Severe Brain Injury - Charlotte Maschke; Loretta Norton; Catherine Duclos; Miriam Han; Kira Dolhan; Geoffrey Laforge; Allison Frantz; Xiaoyu Wang; Hassan Al‐Hayawi; Tianyu Zhang; Raphaël Lavoie; Adrian M. Owen; et al. (Annals of Clinical and Translational Neurology)
ABSTRACT Objective Accurate assessment of the level of consciousness and potential to recover in patients with severe brain injury underpins crucial decisions in the intensive care unit but remains a major challenge for the clinical team. The neurological wake‐up test is a widely used assessment tool. However, many patients' behavioral responses during a short interruption of sedation are ambiguous or absent, yielding little prognostic value. This study assesses the brain's electroencephalogram response during an interruption of propofol sedation to complement behavioral assessment during the neurological wake‐up test to predict survival, recovery of consciousness, and long‐term functional outcomes in patients with acute severe brain injury. Methods We recorded 128‐channel EEG from 41 severely brain‐injured patients during a clinically indicated neurological wake‐up test. Behavioral assessment was performed before and after interruption of propofol sedation, using the Glasgow Coma Scale. Brain response to sedation interruption was quantified using EEG power, spatial ratios, and the spectral exponent. Results Recovery of responsiveness during the neurological wake‐up test is reflected in participants' brain response to sedation interruption. Electrophysiological patterns can be decoupled from participant behavioral response, with some individuals demonstrating neurophysiological signs of waking up despite an absent behavioral response. Using the brain response to complement behavioral assessment improved prognostic value, distinguished patients according to survival and outperformed outcome predictions of the patients' attending physician. Interpretation EEG can complement behavioral assessment during the neurological wake‐up test to improve prognostication, inform clinicians, family members, and caregivers, and to set realistic goals for treatment and therapy.